The concept of grave torment: A comparison of the thoughts of Ibn Qayyim Al-Jauziyah and Albert Bandura - Nada Shobah; Achmad Khudori Soleh (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Abstract: The torment of the grave is the consequence and punishment for servants of every deed done in the world. The similarity of context related to grave torments between Ibn Qayyim al-Jauziyah's perspective and Albert Bandura's social theory of learning has gaps of difference that form the basis of this research, so the author conducts a comparative analysis from the point of view of the two characters. This article aims to find differences and similarities in the concept of strengthening from the comparative analysis of Ibn Qayyim al-Jauziyah's thoughts on the torment of the grave with Albert Bandura's thoughts. This study uses qualitative research methods with comparative analysis techniques. The results show that Ibn Qayyim al-Jauziyah's thoughts on grave punishment have the same concept as Albert Bandura's social learning theory, namely grave punishment as a form of reinforcement so that individuals do not repeat bad behavior. The difference lies in the form of reinforcement, the form of change, the timing of administration, behavioral patterns, the function of observation in modeling, model classification, and reinforcement success.Keywords: Torment of the Grave; Ibn Qayyim al-Jauziyah; Albert Bandura.Abstrak:Siksa kubur merupakan konsekuensi yang harus diterima dan seakan menjadi pusnishment bagi seorang hamba sebagai bentuk balasan dari setiap tingkah laku yang dilakukannya selama hidup di dunia. Kesamaan konteks terkait siksa kubur antara perspektif Ibnu Qayyim al-Jauziyah dengan teori sosial belajar Albert Bandura memiliki celah perbedaan yang menjadi dasar penelitian ini sehingga penulis melakukan analisis komparatif dalam sudut pandang kedua tokoh. Adapun tujuan penulisan artikel ini adalah menemukan perbedaan dan persamaan konsep penguatan dari analisis komparatif pemikiran Ibnu Qayyim al-Jauziyah mengenai siksa kubur dengan pemikiran Albert Bandura. Penelitian ini menggunakan metode penelitian kualitatif dengan teknik analisa komparatif. Hasil penelitian menunjukkan bahwa pemikiran Ibnu Qayyim al-Jauziyah mengenai siksa kubur memiliki kesamaan konsep dalam teori social learning milik Albert Bandura, yakni siksa kubur sebagai bentuk penguatan agar individu tidak mengulangi perilaku yang buruk. Perbedaannya terletak pada aspek bentuk penguatan, bentuk perubahan, waktu pemberian, pola perilaku, fungsi pengamatan dalam pemodelan, klasifikasi model, dan keberhasilan penguatanKata Kunci: Siksa Kubur; Ibn Qayyim al-Jauziyah; Albert Bandura.